Understanding mafia networks - Musotto, Roberto (Organizational crime, 2023)
"The Sicilian Mafia is the most famous criminal organisation in the world. While its own code of honour, rustic chivalry and violence methods have been adopted by other illicit groups, very little is known about how the Mafia, Cosa Nostra, is actually organised and embedded in its territory. Who runs the day-to-day operations? What does it take for a Mafioso to raise the ranks and become a boss? How can the organisation protect itself and re-group after arrests? This book explores for the first time the structure of this criminal organisation through the lens of spatial and social network analysis and answers these questions. This is done by looking at the relationships of 176 members of the organisation that have been recently involved in building the Cupola, the highest ruling and judicial body in the organisation. Starting from the arrest warrant that uncovered this criminal restructuring, a method and several alternatives are offered, explained and commented on how to analyse and visualise criminal networks. The book confirms the assumption that the Sicilian Mafia is a criminal organisation that is deeply rooted in its territory. Mafiosi live, work and interact only in the remit of their own neighbourhood. Bosses are evasive, even to their own affiliates, and mid-level members are in charge of keeping the whole network operational. This book is particularly useful to students, researchers and law enforcement agencies that look at new ways to understand and disrupt the operations and structure of criminal organisations around the world"--